Annual Plan 1971-72 Laccadive, Minicoy and Amindivi Islands Administration - Planning Commission (Planning Commission, 1971)
It has hence been decided to tats up intensive rat control campaigns in all islands by placing warfarin blocks on treetops and homesteads to be supplemented by gassing, trapping and banding. Bombay locusts which are endemic in Kadmat and Agatti also requires constant watch. Rhinocerous bettles and stem bleeding disease requires to be controlled in all the Islands.
Laccadive, Minicoy and Amindivi Islands Administration